STATE SOVEREIGNTY IN THE CONTEXT OF FORMING POLITICAL SPACE IN THE INFORMATION AGE: MAIN DEVELOPMENT TRENDS - Brynza, Kostiantyn (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
The features of the transformations of state sovereignty in the information age are considered. Principled approaches to defining sovereignty and the state in political philosophy are highlighted. The emphasis is on the fact that the state must solve the problem of streamlining the activities of all existing institutions, so that the people benefit from their activities. The conditions that influence the components of state sovereignty, primarily the characteristics of the state, are analyzed. A comparative measurement of the classical understanding of sovereignty and related practices with its modern definition is provided. Particular attention is paid to the formation of political space. It is determined that the sovereignty of the state was classically associated with the spatial definition of the sphere of implementation of sovereign power, with a territory defined by borders. In the issue of the evolution of sovereignty, it is emphasized that the national-territorial identity that accompanies the processes of the formation of modern states is no longer based only on territorial markers, visualized symbols of the embodiment of power – the personalities of the rulers (typical of previous eras), but on the presence of common values ​​and cultural codes for large communities of people. The existence of a common socio-cultural field in society is becoming more relevant, integrating each individual into a specific community with its own interests – the nation, which is certainly strengthened and supported by the state. The information age is shaping a new dimension of space that corresponds to its fundamental qualities, when information, knowledge, and communication become the driving forces of productivity and power. Power, as the substantive core of state sovereignty at the information stage of development, is actively manifested through the ability to produce and control the values and cultural codes of society. The achievements of informatization and digitalization of public life as an important trend of modern development are dialectically connected with the processes of another leading trend – globalization.It is determined that the contradictions and conflicts of universalism and particularism shape the logic of the modern reformatting of the world order, set the tension of instability, and increase the risks of uncertainty and unpredictability of the consequences of political decisions and actions. The complexity of the architecture of the distribution of power in the world, the latency and uncoordinated processes of interaction, the multilevel nature and contradictions of simultaneously existing identities are important global trends. The sovereignty of the state requires the powerful formation and support of ideological components, the protection of the unique values and cultural codes of the nation, which define the modern political space, which is largely virtualized.